A study on the tribological property of MoS2/Ti–MoS2/Si multilayer nanocomposite coating deposited by magnetron sputtering. Issue 16 (5th March 2020) - Kong, Ning; Wei, Boyu; Li, Dongshan; Zhuang, Yuan; Sun, Guopeng; Wang, Bo
Abstract : Pure MoS2 coatings are easily affected by oxygen and water vapor to form MoO3 and H2 SO4 which cause a higher friction coefficient and shorter service life. Abstract : Pure MoS2 coatings are easily affected by oxygen and water vapor to form MoO3 and H2 SO4 which cause a higher friction coefficient and shorter service life. In this work, five kinds of MoS2 /Ti–MoS2 /Si multilayer nanocomposite coatings have been deposited by using unbalanced magnetron sputtering with different modulation period ratios. The tribological tests and nano-indentation experiments have been carried out in order to study the tribological and mechanical properties of the multilayer nanocomposite coating. The results show that the hardness and internal stress of the multilayer nanocomposite coatings are superior to those of the pure MoS2 coating. The polycrystalline columnar structures are effectively inhibited and the coating densification increases due to the multilayer nanostructure and the doped elements of Ti and Si. The nanocomposite coating with a modulation period ratio of 100 : 100 shows the lowest friction coefficient and wear rate. The multilayer nanocomposite coatings exhibit excellent tribological property under a heavy constant load. Interfaces in multilayer nanostructure coating is able to hinder the dislocations motion and the crack propagation. The doped elements of Ti and Si with nano-multilayer structure enhances the mechanical and tribological properties of MoS2 coating. This study provides guidelines for optimizing the mechanical and tribological properties of MoS2 coating.